Impact of Foliar Application of Potassium Silicate on Growth and Productivity of Wheat by Alleviating High Temperature Stress: Potassium silicate mitigates heat stress in wheat - Kaur, Maninder; Deol, J S; Gupta, Neha; Mavi, G S (Journal of Cereal Research, 2025)
High temperature stress significantly affects the crop at every zodiac stage either directly or indirectly by altering hydration status. To evaluate the role of potassium silicate to mitigate high temperature stress in wheat, the study was conducted during Rabi 2021-22 & 2022-23 at Punjab Agricultural University, Ludhiana, Punjab, India. An experiment laid out in split plot design comprised of four environments i.e. 25th October (D1 ), 5th November (D2 ), 15th November (D3)and 25th November (D4) in main plots and eight potassium silicate (K2SiO3) treatments i.e. control (T1), 2% potassium silicate (K2SiO3 ) at boot leaf (T2), 2% K2 SiO3 at anthesis (T3), 3% K2SiO3 at boot leaf stage (T4), 3% K2SiO3 at anthesis (T5,) 2% K2SiO3 at boot leaf stage + anthesis, (T6) 3% K2SiO3 at boot leaf stage + anthesis (T7 ) and 2% KNO3 at boot leaf stage + anthesis (T8) in sub-plots. The study found that D1 planting results in 8-11 and 6-7 per cent increase in leaf area index (LAI) and dry matter accumulation (DMA), respectively, whereas 20-26 per cent LAI increase was recorded with foliar spray of 3% potassium silicate at boot leaf + anthesis stages contributed for yield enhancement. It is concluded that early sowing of wheat on 25th October, combined with foliar application of 3% potassium silicate at booting + anthesis stages, effectively mitigates the adverse effects of high-temperature stress and contributes to improved growth, yield attributes, and overall productivity of wheat.